2007
DOI: 10.1111/j.1365-2672.2006.03133.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Iss and Bor on the surface of Escherichia coli

Abstract: Aims:  To confirm the presence of Iss and Bor on the outer membrane of Escherichia coli using Western blots of outer membrane protein (OMP) preparations and fluorescence microscopy, and explore the use of fluorescence microscopy for the detection of avian pathogenic E. coli (APEC) and diagnosis of avian colibacillosis. Methods and Results:  Knockout mutants of iss and bor were created using a one‐step recombination of target genes with PCR‐generated antibiotic resistance cassettes. Anti‐Iss monoclonal antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…Interestingly, although there has been some development of vaccines to alleviate this problem, none have been effective in fully controlling this infection or disease (Lynne et al, 2012;Lynne et al, 2007). Despite the intensive research globally, the genetic diversity of APEC make it hard to reach a consensus on definition of APEC (Johnson et al, 2008b;Lynne et al, 2007;Rodriguez-Siek et al, 2005a). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, although there has been some development of vaccines to alleviate this problem, none have been effective in fully controlling this infection or disease (Lynne et al, 2012;Lynne et al, 2007). Despite the intensive research globally, the genetic diversity of APEC make it hard to reach a consensus on definition of APEC (Johnson et al, 2008b;Lynne et al, 2007;Rodriguez-Siek et al, 2005a). …”
Section: Discussionmentioning
confidence: 99%
“…These VGs are frequently associated with septicaemia as they assist the bacteria in avoiding being killed by the essential defence mechanisms present in the blood, including complement, antimicrobial peptides and other serum components (Boerlin and Reid-Smith, 2008;Jacobson et al, 1992;Jeffrey et al, 2002;Nolan et al, 2003). Several investigations have reported serum resistance VGs are widespread among APEC in comparison with AFEC and have suggested that these VGs contribute to APEC pathogenicity (Delicato et al, 2003;Dozois et al, 1992;Dziva and Stevens, 2008;Lynne et al, 2007;Mellata et al, 2003;Mellata et al, 2012;Nolan et al, 2002;Ozawa et al, 2008;Rocha et al, 2008;Rodriguez-Siek et al, 2005a;Skyberg et al, 2008;Tivendale et al, 2004;Wooley et al, 1992;Yaguchi et al, 2007;Yang et al, 2004;Zhao et al, 2005). Several VGs have been linked with serum resistance mechanisms and the association of each of the serum resistance VGs with APEC pathogenicity mechanisms have also been independently studied (Nakazato et al, 2009;Rocha et al, 2008).…”
Section: Serum Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…The gene is found in most APEC regardless of its host type of origin, lesion of origin, or serogroup (40) and is linked to large, transmissible virulence plasmids which appear to be the defining trait of the APEC pathotype (23,40). Iss, the protein it encodes (4,16), occurs in APEC's outer membrane where it is readily accessible to the host defenses (31). This strong association between iss and APEC, along with outer membrane location of Iss, suggested that iss-centric strategies might be useful in colibacillosis control.…”
mentioning
confidence: 99%